Mechanical Mechanism Analysis of Roof Fracture Evolution in Stope with Variable Length Based on Elastic-Plastic Structure Theory. (4th April 2022) - Wang, Xinfeng; Lu, Mingyuan; Wei, Rui; Wang, Zhaofeng; Li, Shan
Abstract : Stope with variable length is formed by length change of mining face due to the irregular distribution of geological rock pillars, which is a typical representative of complex coal seam mining. According to the geometric characteristics and mechanical boundaries of each mining stage of stope with variable length, the roof structure models with four boundary conditions were established and solved successively by using the small deflection thin plate bending theory. Combined with the simulated images of MATLAB and FLAC 3D, the fracture laws and corresponding engineering phenomena were analyzed. According to the characteristics of roof rock pressure zoning, the overburden structure pressure model of "three stopes, three areas, and three structures" is constructed. The research shows that the traditional "O-X" fracture occurs in the roof of small mining stope. For the cracks generated by prolonged "O-X" fracture and drift "O-X" fracture in mutative mining stope are similar to the crack development characteristics of large mining stope, so they are integrated into full-scale mining stope. The full-scale mining stope roof is broken in "X-O" shape, and the crack continues to develop to produce extended fracture, forming the roof fracture theory of "two stopes and two laws." The research conclusion strongly reveals the failure law of roof from tension instability to plastic fracture and abnormal ground pressure during mining in stope with variable length. It provides a basis for exploring the essence of overburden migration in stope with variable length and strengthening the roof prevention and control theory under the occurrence conditions of deep complex coal seams.